Eruption Pattern of Permanent Molars among School Children in Chennai - Daniel Rajendran T (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Estimation of the age of an individual is essential investigation in medicolegal cases, especially involving children and adolescents. Among the various factors used for age estimation, eruption of permanent teeth is one of them. Several factors influence the eruption of teeth, including genetic, nutritional and hormonal. This study was carried out to analyze the pattern of eruption of permanent teeth among school going children in urban Chennai. Method: This cross sectional study was carried out among 983 school children between the age group of 4-14 years. Two schools, one belonging to the lower socioeconomic status and the other belonging to the higher socioeconomic status were taken up for this study. Eruption of permanent teeth were examined clinically. Results: Majority of the first molars erupted by7-7.5 years of age (95%) while majority of the central incisors erupted between 8-9 years. Lateral incisors were completely erupted between 9.5-10 years and first premolar were completely erupted between 12.5-12.9 years. Both second premolar and canine erupted by 13.5-13.9 years. Conclusion: The visual observation of eruption of permanent teeth is a non invasive procedure and does not require any special machines like that of radiography. This method of assessing the age of the individual is considerably easier, economical and safe. Hazards of exposing the individual to radiation can be prevented.